Perspectives for immunotherapy in noninfectious immune mediated uveitis. (2nd September 2021) - Touhami, Sara; Gueudry, Julie; Leclercq, Mathilde; Touitou, Valérie; Ghembaza, Amine; Errera, Marie Hélène; Saadoun, David; Bodaghi, Bahram
ABSTRACT: Introduction : Noninfectious uveitis (NIU) is one of the leading causes of blindness worldwide. In adult patients, anterior NIU is usually managed with topical corticosteroids. In intermediate, posterior uveitis. and panuveitis, systemic corticosteroids are used especially in case of bilaterality or association with systemic disease. Biotherapies are recommended in case of inefficacy or intolerance to corticosteroids or conventional immunosuppressive drugs. Anti-TNF-α agents are by far the most widely used biotherapies. In case of failure or poor tolerance to anti-TNF-α, new targeted therapies can be proposed. Areas covered : We present and discuss an updated overview on biologics and biotherapies in NIU. Expert opinion : In case of dependency to systemic or intravitreal steroids, sight-threatening disease, and/or failure of conventional immunosuppressive drugs, anti-TNF-α are used as first-line biologics to achieve quiescence of inflammation. Anti-interleukin-6 is another option that may be proposed as first-line biologic or in case of poor efficacy of anti-TNF-α. Interferon can be directly proposed in specific indications (e.g. refractory macular edema, sight-threatening Behçet's uveitis). In the rare cases that remain unresponsive to traditional biotherapies, novel molecules, such as Janus-associated-kinase and anti-phosphodiesterase-4-inhibitors can be used. Therapeutic response must always be evaluated by clinical and appropriate ancillary investigations.